Glasnost : Soviet Non-Conformist Art from the 1980s - Joseph, Backstein; Haunch of Venison, London; Boris, Groys; Ekaterina, Degot; Miall, Nina; Olga, Sviblova (London : Haunch of Venison)
Abramishvili, Giya (Guram) ; Albert, Yuri ; Basilev, Sergey ; Belenok, Pyotr ; Bezukladnikov, Andrey ; Borisov, Sergey ; Brodsky, Alexander ; Brusilovsky, Anatoly ; Bugaev, Sergey ; Bulatov, Erik
Glasnost Soviet Non-Conformist Art from the 1980s, Haunch of Venison, London, 16 April - 23 June 2010
kunstcatalogus
Keywords: Soviet Union